2005
DOI: 10.1007/s10495-005-0803-9
|View full text |Cite
|
Sign up to set email alerts
|

Smac/DIABLO and cytochrome c are released from mitochondria through a similar mechanism during UV-induced apoptosis

Abstract: During apoptosis, a key event is the release of Smac/DIABLO (an inhibitor of XIAP) and cytochrome c (Cyt-c, an activator of caspase-9) from mitochondria to cytosol. It was not clear, however, whether the releasing mechanisms of these two proteins are the same. Using a combination of single living-cell analysis and immunostaining techniques, we investigated the dynamic process of Smac and Cyt-c release during UV-induced apoptosis in HeLa cells. We found that YFP-labeled Smac and GFP-labeled Cyt-c were released … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 28 publications
6
37
1
Order By: Relevance
“…Live cell imaging was used on either staurosporine (STS)-or actinomycin D-treated HeLa cells to show there was coincident and efficient release of cyt c, Smac, Omi, and adenylate kinase II (a nonapoptogenic IMS protein) (25). In accordance with this finding, when HeLa cells were exposed to UV light, simultaneous redistribution of cyt c and Smac was observed (27). However, application of other apoptotic inducers to HeLa cells or other cell types exposed to a variety of treatments reveals that differential release of cyt c and Smac occurs.…”
Section: Redistribution Of Ims Proteinsmentioning
confidence: 78%
See 1 more Smart Citation
“…Live cell imaging was used on either staurosporine (STS)-or actinomycin D-treated HeLa cells to show there was coincident and efficient release of cyt c, Smac, Omi, and adenylate kinase II (a nonapoptogenic IMS protein) (25). In accordance with this finding, when HeLa cells were exposed to UV light, simultaneous redistribution of cyt c and Smac was observed (27). However, application of other apoptotic inducers to HeLa cells or other cell types exposed to a variety of treatments reveals that differential release of cyt c and Smac occurs.…”
Section: Redistribution Of Ims Proteinsmentioning
confidence: 78%
“…This was demonstrated by real-time confocal photomicrography of live cells expressing fluorescently labeled cyt c and/or Smac while they underwent apoptosis (24)(25)(26)(27). These studies also showed that after the initiation of apoptosis, the onset of release of IMS proteins was not predicable and took place at widely different time intervals after the addition of the apoptotic stimulus.…”
Section: Redistribution Of Ims Proteinsmentioning
confidence: 92%
“…A recent study showed that SMAC release is suppressed in cytochrome cdeficient cells (Hansen et al, 2006). It has been shown that SMAC and cytochrome c are released together from the mitochondria during UV-induced apoptosis (Zhou et al, 2005). Therefore, questions remain as to how SMAC release affects other mitochondria-related events during apoptosis, and whether its function in regulating mitochondrial events is related to IAP inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported both that Smac/DIABLO is released independently of cytochrome c (Deng et al, 2002) and simultaneously with it (Zhou et al, 2005). This discrepancy might be the result of different mechanisms of release after a specific stimulus that eventually converge, as suggested by the requirement of caspase activity for Smac/DIABLO release but not for cytochrome c release (Adrain et al, 2001).…”
Section: Introductionmentioning
confidence: 99%